Radiografers oppfatninger av suboptimale henvisninger innen konvensjonell røntgen - en kvalitativ studie - Abohaikel, Alaa Sadiq; Musa, Huda Hussein; Lysdahl, Kristin Bakke (Radiography Open, 2018)
Abstract: Title: Radiographers’ perception of suboptimal referrals for plain radiography – a qualitative study. Introduction: Adequately filled in radiology requests forms are crucial for the quality of conducting and reporting examinations. Still suboptimal referrals occur. The knowledge of how the referrals are assessed handled in the radiological department is limited, in particular the role of the radiographers. The purpose of this study was to investigate how radiographers understand, experience and act upon suboptimal referrals and how this influence their work. Methods and Materials: A semi-structured interview guide was developed and applied in individual interviews with five radiographers in south-east Norway. The radiographers had different length of employment and experience in performing plain radiographs. The interviews were transcribed and analyzed using a thematic analysis method. Results: Five main categories were identified from the interviews. 1) Scope and type of referral quality problems, where the problem is recognised, mainly due to missing clinical information, which is reported to occur frequently, particularly in referrals for control examinations. 2) Communication experiences and approaches towards patients, experienced colleges or radiologists, when seeking to substitute missing/wrong referral information. 3) Consequences of inappropriate referrals, in shape of unwarranted examinations, waste of time, and reduced job satisfaction. 4) Perceived responsibility for optimisation and justification of examinations. 5) Strategies to overcome the problem, through leadership and co-operation between radiographers, radiologists and referring physicians. Conclusion: Suboptimal referral quality influence the radiographers work. They recognize it as a commonplace problem with implication for quality patient care, own work-situation and -satisfaction and economically for health society. Increased interdisciplinary co-operation may improve the quality of the referrals.